The Effect of Cone Opsin Mutations on Retinal Structure and the Integrity of the Photoreceptor Mosaic - Carroll, Joseph; Dubra, Alfredo; Gardner, Jessica C.; Mizrahi-Meissonnier, Liliana; Cooper, Robert F.; Dubis, Adam M.; Nordgren, Rick; Genead, Mohamed; Connor, Thomas B.; Stepien, Kimberly E.; Sharon, Dror; Hunt, David M.; et al. (Investigative ophthalmology & visual science, 2012)
To evaluate retinal structure and photoreceptor mosaic integrity in subjects with OPN1LW and OPN1MW mutations. Eleven subjects were recruited, eight of whom have been previously described. Cone and rod density was measured using images of the photoreceptor mosaic obtained from an adaptive optics scanning light ophthalmoscope (AOSLO). Total retinal thickness, inner retinal thickness, and outer nuclear layer plus Henle fiber layer (ONL+HFL) thickness were measured using cross-sectional spectral-domain optical coherence tomography (SD-OCT) images. Molecular genetic analyses were performed to characterize the OPN1LW/OPN1MW gene array. While disruptions in retinal lamination and cone mosaic structure were observed in all subjects, genotype-specific differences were also observed. For example, subjects with "L/M interchange" mutations resulting from intermixing of ancestral OPN1LW and OPN1MW genes had significant residual cone structure in the parafovea (∼25% of normal), despite widespread retinal disruption that included a large foveal lesion and thinning of the parafoveal inner retina. These subjects also reported a later-onset, progressive loss of visual function. In contrast, subjects with the C203R missense mutation presented with congenital blue cone monochromacy, with retinal lamination defects being restricted to the ONL+HFL and the degree of residual cone structure (8% of normal) being consistent with that expected for the S-cone submosaic. The photoreceptor phenotype associated with OPN1LW and OPN1MW mutations is highly variable. These findings have implications for the potential restoration of visual function in subjects with opsin mutations. Our study highlights the importance of high-resolution phenotyping to characterize cellular structure in inherited retinal disease; such information will be critical for selecting patients most likely to respond to therapeutic intervention and for establishing a baseline for evaluating treatment efficacy.